A multi‐method review of home‐based chemotherapy. (6th November 2015) - Evans, J.M.; Qiu, M.; MacKinnon, M.; Green, E.; Peterson, K.; Kaizer, L.
Abstract : This study summarises research‐ and practice‐based evidence on home‐based chemotherapy, and explores existing delivery models. A three‐pronged investigation was conducted consisting of a literature review and synthesis of 54 papers, a review of seven home‐based chemotherapy programmes spanning four countries, and two case studies within the Canadian province of Ontario. The results support the provision of home‐based chemotherapy as a safe and patient‐centred alternative to hospital‐ and outpatient‐based service. This paper consolidates information on home‐based chemotherapy programmes including services and drugs offered, patient eligibility criteria, patient views and experiences, delivery structures and processes, and common challenges. Fourteen recommendations are also provided for improving the delivery of chemotherapy in patients' homes by prioritising patient‐centredness, provider training and teamwork, safety and quality of care, and programme management. The results of this study can be used to inform the development of an evidence‐informed model for the delivery of chemotherapy and related care, such as symptom management, in patients' homes.